2016
DOI: 10.1063/1.4964674
|View full text |Cite
|
Sign up to set email alerts
|

Role of dynamic heterogeneities in crystal nucleation kinetics in an oxide supercooled liquid

Abstract: The temperature at which the classical critical nucleus size is equal to the average size of the cooperatively rearranging regions (CRR) in a supercooled liquid has been referred to as a "cross-over" temperature. We show, for the first time, using published nucleation rate, viscosity, and thermo-physical data, that the cross-over temperature for the lithium disilicate melt is significantly larger than the temperature of the kinetic spinodal and is equal or close to the temperature corresponding to the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…While sometimes explained as experimental error, the effect is far outside experimental error in these mBaO•nSiO2 studies. Some investigators have tested possible theoretical explanations such as elastic stress, changing size of structural units, spatial heterogeneity and dynamical heterogeneity to account for the effect [27,[29][30][31], but the correct explanation remains unclear due to the lack of experimental or modeling evidence.…”
Section: Results From Methods #2mentioning
confidence: 99%
“…While sometimes explained as experimental error, the effect is far outside experimental error in these mBaO•nSiO2 studies. Some investigators have tested possible theoretical explanations such as elastic stress, changing size of structural units, spatial heterogeneity and dynamical heterogeneity to account for the effect [27,[29][30][31], but the correct explanation remains unclear due to the lack of experimental or modeling evidence.…”
Section: Results From Methods #2mentioning
confidence: 99%
“…In Ref. 29, we showed that the crossover temperature for that liquid is significantly larger than the temperature of the (estimated) kinetic spinodal and is equal or close to the temperature corresponding to the maximum in the experimentally observed nucleation rates. However, in Ref.…”
Section: Literature Reviewmentioning
confidence: 78%
“…15 In Ref. 29, we made a rough estimate of T KS and demonstrated that it should likely be located below the temperature of (experimental) the nucleation rate maximum for one silicate liquid, but we did not compare it with T K . Finally, in a recent paper, 30 the authors concluded that there is no sign of a thermodynamic or even a "pseudo" spinodal in melt crystallization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations